Making the “digital leap” in Finnish schools - Reijo Kupiainen (Nordisk tidsskrift for pedagogikk og kritikk, 2022)
In 2015, the Finnish Ministry of Education and Culture launched a digitalisation project called the “digital leap.” The objective of this project was to help schools quickly modernise their information and communication technology (ICT) infrastructure and pedagogy. Finnish schools have had many digitalisation projects, but the use of ICT in teaching and learning has been relatively small scale compared with other Nordic countries. Finnish teachers have autonomy for pedagogical decisions and have even abstained from top-down governing and “dumping” digital technology to schools. This article examines the challenges of school digitalisation in Finland, obstacles the teachers face in the use of ICT in education, and some perspectives on the teachers’ possibility to participate in the digitalisation process. This article is based on research done in Educating for Future Literacies Research Group (EduLit) at Tampere University. The research indicates that teachers’ professional capital plays an important role in the digitalisation process.